A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia - Sehnal, Richard (Zootaxa, 2017)
The Afrotropical genus Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) was recently treated by Lacroix (2015), who keyed and figured most of the known species and divided the genus into six species groups based on the number of antennomeres, shape of male genitalia and number of teeth on the protibia. Unfortunately, Lacroix (2015) overlooked two earlier papers by Harrison (2014a, 2014b). Harrison (2014a, 2014b) provided a phylogenetic analysis of the tribe, synonymised Hypopholis Erichson, 1847 with Pegylis, and redescribed the three known South African species of Pegylis. Based on these papers, the genus Pegylis currently contains 37 species.